In the dust of this planet - Thacker, Eugene (Winchester : Zero Books, 2011)
Thacker besteedt in dit boek o.a. aandacht aan "occulte filosofie" en de "horror van de theologie".
Keywords: Horror films; Horror in literature; Metaphysics in literature; Philosophy in literature; Supernatural in literature